Molecular and biological characterization of transforming growth factor-β homolog derived from Trichinella spiralis - Salisa Chaimon; Orawan Phuphisut; Onrapak Reamtong; Sumate Ampawong; Kamonpan Fongsodsri; Pathanin Chantree; Jeeraphong Thanongsaksrikul; Preeyarat Malaithong; Suthasinee Sreesai; Wanchai Maleewong; Lakkhana Sadaow; Pongsakorn Martviset; et al. (Scientific Reports)
Abstract The cytokine homologs, particularly transforming growth factor (TGF)-β, is a crucial immunomodulatory molecule and involved in growth and developmental processes in several helminths. In this study, the basic properties and functions of T. spiralis TGF-β homolog 2 (TsTGH2) were characterized using bioinformatics and molecular biology approaches. Bioinformatics analyses indicated that TsTGH2 belongs to the TGF-β subfamily. Recombinant TsTGH2 (rTsTGH2) expressed in Escherichia coli was used to produce a polyclonal antibody (pAb) in mice. Western blot and immunolocalization using pAb detected native TsTGH2 in crude worm antigens from muscle larvae and adults, showing it was mainly localized in the body wall muscles and the epithelia of the ovary and uterus. To assess the interplay between TsTGH2 and the human TGF-β signaling pathway, rTsTGH2 produced in a HEK293T cell was incubated with the SBE luciferase-HEK293 cell. The result indicated a significant increase in luciferase activity after treatment with rTsTGH2 compared to untreated control (p < 0.05). In conclusion, these findings are the first to characterize the basic properties and functions of TGF-β homologs in T. spiralis, demonstrating their interaction with the human TGF-β receptor. Further investigation is required to identify and optimize an appropriate expression system or conditions for TsTGH2. Additionally, studies are needed to clarify the specific role of native TsTGH2 in parasite development and host immunomodulation.